The Influence of Quich Ratio, Gross Profit Margin and Total Asset Turnover on Profit Growth at PT. Food Sejahtera Tbk - Fadilatul Kodriah; Aliah Pratiwi; M. Rimawan (Journal JEKAMI, 2026)
This study aims to examine the effect of financial performance indicators, namely Quick Ratio (QR), Gross Profit Margin (GPM), and Total Asset Turnover (TATO), on profit growth at PT Food Sejahtera Tbk, a company listed on the Indonesia Stock Exchange during the 2014–2023 period. The research employs a quantitative associative approach using secondary data derived from the company’s annual financial statements. The analysis method applied is multiple linear regression, supported by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, as well as hypothesis testing through t-test and F-test. The results indicate that partially, QR, GPM, and TATO do not have a significant effect on profit growth. Simultaneously, these variables also show no significant influence on profit growth. The coefficient of determination (R²) value of 0.547 suggests that 54.7% of the variation in profit growth can be explained by the three independent variables, while the remaining 45.3% is influenced by other factors not included in this study. These findings imply that liquidity, profitability, and asset utilization efficiency are not the main determinants of profit growth in the observed company. Therefore, it is recommended that management consider other strategic factors such as operational efficiency, marketing strategies, and product innovation to enhance profit growth performance in the future.